2020
DOI: 10.1101/2020.06.11.20128249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolution and epidemic spread of SARS-CoV-2 in Brazil

Abstract: Brazil currently has one of the fastest growing SARS-CoV-2 epidemics in the world. Due to limited available data, assessments of the impact of non-pharmaceutical interventions (NPIs) on virus transmission and epidemic spread remain challenging. We investigate the impact of NPIs in Brazil using epidemiological, mobility and genomic data. Mobility-driven transmission models for Sao Paulo and Rio de Janeiro cities show that the reproduction number (Rt) reached below 1 following NPIs but slowly increased to values… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
98
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 33 publications
(31 reference statements)
9
98
0
14
Order By: Relevance
“…These observations are in line with the known epidemiology of the pandemic (5). Furthermore, the analysis of genomic data has shown that Peruvian isolates were widely distributed across the phylogenetic tree suggesting multiple, independent introductions, designed as nodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) with over 70% of statistical support from ML ( Figure 1A and Table 1). Similar to these introductions it has been reported in other countries such as Brazil (6), Colombia (7) and the USA (8).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…These observations are in line with the known epidemiology of the pandemic (5). Furthermore, the analysis of genomic data has shown that Peruvian isolates were widely distributed across the phylogenetic tree suggesting multiple, independent introductions, designed as nodes (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) with over 70% of statistical support from ML ( Figure 1A and Table 1). Similar to these introductions it has been reported in other countries such as Brazil (6), Colombia (7) and the USA (8).…”
Section: Resultssupporting
confidence: 74%
“…In addition, most introductions into South America countries (e.g. Colombia or Brazil) included European B lineages isolates (6,7,12). However, any other factors might be involved including uneven sampling, chance and epidemiology reasons (13).…”
Section: Resultsmentioning
confidence: 99%
“…An average of 113,821.3 reads were obtained per sample reaching 960.52× of average depth of coverage in the genomes analyzed. We found that two of the SARS-CoV-2 genomes obtained (VEN-89312 and VEN-95072) were identical and belonged to the B1 lineage, while the third (VEN-95070) belonged to the B.1.13 lineage, suggesting two separate introductions ( da Candido et al, 2020 ; Ramirez et al, 2020 ). Phylogenetic analysis revealed that two of the Venezuelan SARS-CoV-2 genomes (VEN-95070 and VEN-95072) closely resembled genomes from neighboring Colombia (Cesar and Norte de Santander Departments) ( Ramirez et al, 2020 ) while the third (VEN-89312) was related to genomes from Brazil ( Fig.…”
Section: Resultsmentioning
confidence: 83%
“…Phylogenetic analysis revealed that two of the Venezuelan SARS-CoV-2 genomes (VEN-95070 and VEN-95072) closely resembled genomes from neighboring Colombia (Cesar and Norte de Santander Departments) ( Ramirez et al, 2020 ) while the third (VEN-89312) was related to genomes from Brazil ( Fig. 1 C) ( da Candido et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…1B) can be inferred using published estimates of the evolutionary rate of the SARS-2 population in the human population, assuming that the pre-and post-emergence rates are the same (Rodríguez-Román and Gibbs, 2020). Various estimates of the SARS-2 evolutionary rate have been published recently; 1.126 x 10 -3 (95 % BCI: 1.03-1.23 x 10 -3 ) substitutions per site per year (s/s/y) (Candido et al, 2020), 1.1×10 −3 s/s/y (95% CI 7.03×10 −4 and 1.5×10 −3 s/s/y) (Duchêne et al, 2020), 9.41×10 -4 s/s/y +/-4.99×10 -5 (Pybus et al, 2020) and 8 x 10 -4 s/s/y (Resende et al, 2020).…”
Section: Resultsmentioning
confidence: 99%